2013
DOI: 10.1111/jop.12078
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of saliva samples from oncological patients treated with 5‐fluorouracil and leucovorin calcium by scanning electron microscopy with energy dispersive system

Abstract: This work presents a chemical and morphological analysis of samples of saliva taken from patients who were under treatment with intravenous chemotherapy with 5-fluorouracil and leucovorin calcium. Samples of saliva were extracted from fifteen patients during the three stages of the treatment: The initial stage (previous to the chemotherapy), the intermediate stage (during the chemotherapy), and the final stage (twenty-one days after finishing the treatment). An amount of 50 μl was collected in each visit. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
0
7
0
3
Order By: Relevance
“…Mazzeo et al . found that in the secretion of the salivary glands, cytostatic metabolites are present, which may further exacerbate inflammation of the mucous membranes of the oral cavity [ 7 ]. Analysis of questionnaires concerning subjective symptoms appearing in the stomatognathic system has shown that patients undergoing anti-neoplastic treatment experience significant discomfort associated with administered therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Mazzeo et al . found that in the secretion of the salivary glands, cytostatic metabolites are present, which may further exacerbate inflammation of the mucous membranes of the oral cavity [ 7 ]. Analysis of questionnaires concerning subjective symptoms appearing in the stomatognathic system has shown that patients undergoing anti-neoplastic treatment experience significant discomfort associated with administered therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One of these materials was rubber, as the most convenient in terms of molding and elastic properties. However, this natural material had significant disadvantages in the form of porosity and chemical instability (Evstratenko et al, 2018;Mazzeo et al, 2013). These and many other factors forced researchers to find more stable, versatile, and hygienic materials for the manufacture of dental products.…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing interest in saliva‐based diagnostics mostly due to a possibility of non‐invasive and easy collection of samples for analysis 48. A number of research groups have been developing analysis procedures for monitoring side effects of drugs 9 or diagnosis of broad range of diseases such as diabetes 10–13 and breast cancer 14.…”
Section: Introductionmentioning
confidence: 99%